Pengaruh Capital Intensity dan Return On Asset terhadap Agresivitas Pajak - Muhammad Bahrudin; Saiful Islam; Dien Noviany Rahmatika (Jurnal Pajak dan Analisis Ekonomi Syariah, 2024)
Tax aggressiveness refers to the behavior of managers to reduce the tax burden on the business for their own benefit, so that it can create conflict between shareholders and managers. This occurs as a result of managers perform tax aggression solely for short-term profits without thinking about the long-term advantages of the business that shareholders anticipated. The purpose of this research is to investigate the impact of capital intensity and return on assets (ROA) on corporation's aggressive taxation whose data comes from relevant journals in 2019-2024. Systematic Literature Review is the research methodology employed in this study (SLR) and a total of 50 articles published from 2019-2024 accredited in SINTA are systematically analyzed in this study. The study's conclusions are Capital Intensity has a favorable impact on tax aggression, this means that the higher the capital intensity of a company, the greater the tax burden aggressiveness executed by the business. While the Return on Assets (ROA) of the company is positive and significant effect on tax aggressiveness, which means the greater the business's ROA, the more aggressive they are towards taxes.